Factors responsible for poor sleep quality in patients with chronic obstructive pulmonary disease. Issue 1 (December 2016) - Chang, Chih-Hao; Chuang, Li-Pang; Lin, Shih-Wei; Lee, Chung-Shu; Tsai, Ying-Huang; Wei, Yu-Feng; Cheng, Shih-Lung; Hsu, Jeng-Yuan; Kuo, Ping-Hung; Yu, Chong-Jen; Chen, Ning-Hung
Abstract Background Sleep disturbance is a common complaint in patients with chronic obstructive lung disease (COPD). However, the factors resulting in sleep disturbance remain unclear. This retrospective, observational, multicenter study aimed to identify the factors associated with sleep disturbance in patients with COPD. Methods The study was a retrospective, observational, and multicenter research. Data including age, sex, body mass index, smoking status, COPD inhaler prescribed, clinical symptoms, pulmonary function tests, medical history of comorbidities, and questionnaires were collected. Parameters including demographics, symptoms, medication, severity, functional classification, and comorbidities were correlated with sleep quality scores. Results Among 377 patients with COPD, 200 (53 %) patients experienced poor sleep quality (Pittsburg Sleep Quality Index scores > 5). A significant difference in sleep quality, as measured by PSQI scores, was noted between groups based on the 2011 Global Initiatives for Chronic Obstructive Lung Disease (GOLD) classification system. The most common sleep disturbances included "getting up to use the bathroom" (70.3 %), "wake up at night or early morning" (40.3 %), and "cough and snore loudly at night" (15.9 %). The use of inhaled corticosteroids, the presence of wheezing, COPD Assessment Test (CAT) scores, and Modified Medical Research Council (mMRC) dyspnea scale scores positively correlated with poor sleep quality (odds ratio: 1.51, 1.66, 1.09, and 1.30, respectively). Upon multivariate analysis, the CAT score was an independent factor for poor sleep quality in these patients. With the exception of sleep problem items, based on the CAT questionnaire, phlegm was significantly higher in COPD patients with poor sleep quality. Conclusions Poor sleep quality is common among patients with COPD and symptoms including wheeze, phlegm, and inhaled corticosteroid use may contribute to poor sleep quality. The CAT score is a good indicator of poor sleep quality in patients with COPD.